Primeiro registro de Guyalna cuta em pinhão-manso no estado de Mato Grosso do Sul - Oliveira, Harley Nonato de; Martinelli, Nilza Maria [UNESP]; Bellon, Patrícia Paula; Maccagnan, Douglas Henrique Bottura (Instituto Agronômico de Campinas, 2012)
Trata-se do primeiro registro de ocorrência de Guyalna cuta (Walker) (Hemiptera: Cicadidae) em pinhão-manso, Jatropha curcas L. (Euphorbiaceae) no Estado de Mato Grosso do Sul. Adultos desse inseto foram observados na parte aérea da planta, durante novembro e dezembro de 2008 e de 2009. em Mato Grosso do Sul, existem plantios comerciais e experimentais do pinhão-manso, tornando-se necessários estudos relacionados a este inseto, a fim de prevenir eventuais danos à cultura.

This is the first record of the occurrence of Guyalna cuta (Walker) (Hemiptera: Cicadidae) in physic nut plants, Jatropha curcas L. (Euphorbiaceae) in the State of Mato Grosso do Sul, county of Dourados. Adults of this insect were observed in the plant canopy during the months of November and December in 2008 and 2009. As there are commercial and experimental plantations of physic nut in Mato Grosso do Sul, further studies about this insect are necessary for preventing eventual damage to crop production.
First record of Guyalna cuta on physic nut in Mato Grosso do Sul state
Keywords: Hemiptera; Cicadidae; cigarra; Jatropha curcas; ocorrência; Hemiptera; Cicadidae; Cicada; Jatropha curcas; occurrence